Impoliteness – a challenge to interpreters’ professionalism - Felberg, Tatjana R. (FLEKS - Scandinavian Journal of Intercultural Theory and Practice, 2016)
This article examines interpreters’ perceptions of impoliteness in interpreter-mediated interactions in public sector settings in Norway. The analysis is based on a survey conducted in June 2014, involving 28 interpreters from/to Bosnian/Croatian/ Montenegrin/Serbian and Norwegian. The analytical method is based on the theory of impoliteness and the rapport management model. The study has a discursive, data-driven and bottom-up approach. The study is motivated by challenges described by interpreting students who already work as interpreters in the public sector in Norway. These students repeatedly reported to their teachers two types of challenges with “impoliteness”. The first challenge concerns their own experiences with impoliteness from public service users, public service employees, or both. The other type of challenge concerns the very act of interpreting impoliteness. Even though the Guidelines for best practices in interpreting, which define the interpreter’s role and function, address these issues indirectly, interpreters express a need for more specific knowledge and guidance. As no research has been conducted on impoliteness in interpreter-mediated dialogues in the public sector in Norway, a pilot project was set up in order to describe and analyze the phenomenon, as seen from interpreters’ points of view. This article concentrates on the following research questions: How widespread is impoliteness in interpreter-mediated interaction in public sector settings, according to interpreters?, How do interpreters define and exemplify impoliteness? and What strategies do interpreters use for interpreting impoliteness? The findings suggest that impoliteness in the public sector is more widespread than the author expected. The notion of “conflictive talk” playing a central role in various discourses is supported by interpreters’ examples of impoliteness in interpreter-mediated encounters. Interpreters’ examples indicate that impoliteness may create ambiguity on different levels and that being able to cope with it is crucial for doing a good job as an interpreter. Impoliteness is more than swearwords. It is context dependent – whether something is impolite depends on a participant’s evaluation of the situation. Impoliteness is experienced in a number of ways, and the consequences for interpreters of not managing impoliteness range from hurt feelings to a halt in communication. Interpreters use different interpreting strategies while interpreting impoliteness – from interpreting what is being said, to reporting that impolite language is being uttered, to ignoring impoliteness altogether. These strategies can have a direct influence on the outcome of interpreter-mediated institutional dialogues. Insight into interpreters’ as well as the other communication participants’ concerns leads to the next step: developing and systemizing strategies that can help them cope better with these work-related challenges.